A flexible and robust model for low temperature catalytic desorption of CO2 from CO2-loaded amines over solid acid catalysts. (12th October 2017) - Decardi-Nelson, Benjamin; Akachuku, Ananda; Osei, Priscilla; Srisang, Wayuta; Pouryousefi, Fatima; Idem, Raphael
Highlights: An experimentally validated catalyst-aided CO2 desorption model was developed. Both physical and chemical contribution of catalyst to the process were considered. The predicted CO2 production rates agreed well with experimental data. The model provides a tool for process optimization and scale-up. Abstract: A numerical model for catalyst-aided carbon dioxide (CO2 ) desorption from CO2 -loaded aqueous amines solution has been developed. The model includes a hot water-heater and considers phase separation at the top of the desorption column. The model was validated with experimental data obtained from an integrated CO2 capture pilot plant which used 5 M monoethanolamine (MEA) solution with two industrial catalysts, namely, HZSM-5 and γ-Al2 O3 . The model considers the presence of electrolytes and multi-component mass transfer as well as both the physical and chemical contribution of the catalyst in aiding the process. The data obtained from model simulation were in good agreement with the experimental data in terms of CO2 production rates with an absolute average deviation of approximately ±8.9%. The simulation slightly over-predicted the CO2 production rate at the low temperature regime (75 °C) and under-predicted the CO2 production rate at the high temperature regime (95 °C). The developed model provides a range of capabilities for further studies of the catalytic CO2 desorption process.